2016
DOI: 10.30970/cma9.0347
|View full text |Cite
|
Sign up to set email alerts
|

Formation of microstructures in Ti-Cr-V alloys with high hydrogen sorption capacity

Abstract: TiVCr alloys known for their potentially large hydrogen uptake were formulated as (TiCr 1.8) 100-x V x in order to quantify the impact of the vanadium concentration. Parallel to this series of pure ternaries, a second one was synthesized with 4 mol.% of Zr 7 Ni 10 addition. Structural investigation and electrochemical charging with hydrogen revealed a fair dependence of the hydrogen uptake and hydride stability on the vanadium content, but conversely different due to the presence of the Zr-Ni additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Reported methods for improving activation performance include: 1. Introducing various additives such as Hf–Ni, Zr–Ni, LaNi 5 . 2.…”
Section: Introductionmentioning
confidence: 99%
“…Reported methods for improving activation performance include: 1. Introducing various additives such as Hf–Ni, Zr–Ni, LaNi 5 . 2.…”
Section: Introductionmentioning
confidence: 99%
“…Additives could introduce secondary phases which help the first hydrogenation (Miraglia et al, 2012;Bibienne et al, 2015;Kamble et al, 2017). Skryabina et al (Skryabina et al, 2016) melted (TiCr 1.8 ) 100-x V x for x 20, 40, 60, and 80 with 4 mol% Zr 7 Ni 10 and reported the dependence of hydrogen uptake, reversible hydrogen capacity and desorption temperature on the vanadium content, and dependence upon melted with the Zr-Ni additive. Miraglia et al (Kamble et al, 2017) found dramatic improvement in activation when 4 wt% Zr 7 Ni 10 was added to BCC Ti 33 V 30 Cr 37 alloy by induction melting.…”
Section: Introductionmentioning
confidence: 99%